WAYS TO IMPROVE THE LEGAL MECHANISMS FOR GUARANTEEING LOCAL SELF-GOVERNMENT IN VIEW OF THE PRACTICE OF EUROPEAN COUNTRIES - Pavlov , E. (Theory and Practice of Public Administration, 2021)
The article identifies the state of legal mechanisms for guaranteeing local government in Ukraine. The author substantiates the necessity to develop new approaches to the formation and implementation of public policy, which will promote the development of mechanisms to guarantee local self-government and ensure a high legal level of the population. The article proves the necessity to improve the legal mechanisms for guaranteeing local self-government, taking into account the practice of different European countries. The author substantiates necessity for Ukraine in the conditions of decentralization and the necessity to improve legal mechanisms.The author analyzes the latest researches on the development of local self-government in European countries. The article outlines the concepts, functions, responsibilities of local governments.The author mentions European standards for guaranteeing the rights and legitimate interests of individuals in relations with the state and its bodies. The article examines the organization of the procedure of community-government relations. The article defines the conditions of activity of a state body, defines the decision-making procedure of a state body, defines the possibility of civil society to exercise full control over the activities of state bodies.The author proposes to introduce appropriate changes in the mechanism of legal influence, which would provide access for citizens to monitor the needed activities of the leadership of government agencies, the ability to assess the results of their activities and make decisions on their further support. The author notes that the issues of local self-government are currently extremely important for Ukraine and further research will be useful in developing and substantiating effective mechanisms for public control over the activities of representative bodies of local self-government.